Envisioning the past : archaeology and the image - Smiles, Sam; Moser, Stephanie (New interventions in art history., 2005)
Envisioning the Past brings together archaeologists, art historians, and anthropologists to offer new perspectives on the construction of knowledge concerning the antiquity of man. The volume demonstrates the extent to which the visual presentation of archaeological research creates a particular discourse, powerful enough to shape our understanding of archaeological knowledge. No category of images is immune from this process, from site drawings to museum displays and from manuscript illustrations to digital media. Yet, given the frequent use of images as illustrative material in professional archaeological publications, museums, websites, and TV programs, there are important lessons to be learned. If a genuinely unmediated image is impossible, how should images be used? What can we learn from considering the use of images in the past and present that might guide our responsible use of them in the future? Moving beyond unchallenged presumptions about the passivity of the visual record, Envisioning the Past re-evaluates the importance of the image as a key contributor to the reconstruction of the past.